Optimalisasi Pelayanan Publik Dalam Pelaksanaan e-KTP Guna Memperkokoh Ketahanan Wilayah (Studi di Kelurahan Kalibaru Kecamatan Cilodong Kota Depok) - , Muhtarhadi Nursalim; , Prof. Dr. Djoko Soerjo, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objective of this thesis is to understand the public service condition in the implementation of E-KTP at Kalibaru village, identify the obstacles faced, optimum strategic formulation and its implication on the regional resilience. The method applied to this research was qualitative method that described, explained, classified and primary and secondary data conceptualism using words, sentences, pictures, scheme, and table that was implemented through the three steps of qualitative data analysis i.e. the reduction, presentation and verification of data. The public service in the implementation of E_KTP at Kalibaru village was well carried out